Enthesis: not the same in each localisation – a molecular, histological and biomechanical study - CJ Peniche Silva; SA Müller; N Quirk; RE De la Vega; MJ Coenen; CH Evans; ER Balmayor; M van Griensven (European Cells & Materials, 2022)
The interphase between tendon and bone consists of a highly specialised tissue called enthesis. Typically, the enthesis is described as a succession of four different zones: tendon, non-mineralised fibrocartilage, mineralised fibrocartilage and bone. However, the microstructure of the entheses, cellular composition and mechanical properties vary depending on their anatomical location. The present study aimed to characterise three of the most relevant sites of enthesis injury in a rat model: the patellar tendon, the Achilles tendon and the supraspinatus enthesis, in terms of biomechanics, histology and genetic expression. The patellar enthesis presented the highest ultimate load and lowest stiffness of the three, while the supraspinatus was the weakest and stiffest. The histological characterisation revealed key differences at the insertion site for each enthesis. The patellar enthesis showed a large cartilaginous area at the tendon-to-bone interphase whilst this interphase was smaller in the supraspinatus entheses samples. Furthermore, the Achilles tendon enthesis displayed a more abrupt transition from tendon to bone. Additionally, each enthesis exhibited a particular and distinct pattern of expression of tenogenic, chondrogenic and osteogenic markers. This study provided valuable insights for a better understanding of the three entheses at relevant anatomical sites. Moreover, the larger cross-sectional area of the patellar enthesis, the strong mechanical properties and the easier surgical access to this location led to the conclusion that the patellar tendon enthesis site could be most suitable for the development of a preclinical model for general enthesis regeneration studies in rats.